Machine Learning Aided Resilient Spectrum Surveillance for Cognitive Tactical Wireless Networks: Design and Proof-of-Concept - Eli Garlick; Nourhan Hesham; MD. Zoheb Hassan; Imtiaz Ahmed; Anas Chaaban; MD. Jahangir Hossain (IEEE Transactions on Machine Learning in Communications and Networking, 2025)
Cognitive tactical wireless networks (TWNs) require spectrum awareness to avoid interference and jamming in the communication channel and assure quality-of-service in data transmission. Conventional supervised machine learning (ML) algorithm’s capability to provide spectrum awareness is confronted by the requirement of labeled interference signals. Due to the vast nature of interference signals in the frequency bands used by cognitive TWNs, it is non-trivial to acquire manually labeled data sets of all interference signals. Detecting the presence of an unknown and remote interference source in a frequency band from the transmitter end is also challenging, especially when the received interference power remains at or below the noise floor. To address these issues, this paper proposes an automated interference detection framework, entitled $MARSS$ (Machine Learning Aided Resilient Spectrum Surveillance). $MARSS$ is a fully unsupervised method, which first extracts the low-dimensional representative features from spectrograms by suppressing noise and background information and employing convolutional neural network (CNN) with novel loss function, and subsequently, distinguishes signals with and without interference by applying an isolation forest model on the extracted features. The uniqueness of $MARSS$ is its ability to detect hidden and unknown interference signals in multiple frequency bands without using any prior labels, thanks to its superior feature extraction capability. The capability of $MARSS$ is further extended to infer the level of interference by designing a multi-level interference classification framework. Using extensive simulations in GNURadio, the superiority of $MARSS$ in detecting interference over existing ML methods is demonstrated. The effectiveness $MARSS$ is also validated by extensive over-the-air (OTA) experiments using software-defined radios.